Me and God, we are cool: reconciliation between religious and sexual identity among LGBT members - Ivey, Christina L. (Kansas State University, 2012)
Many LGBT members are caught between two seemingly conflicting identities: their religious identity and their sexual identity as a homosexual. This study specifically examines how Christian LGBT individuals attempt to reconcile their identities. In order to uncover the lived experience of LGBT members, qualitative interviews were conducted with eleven members of the LGBT community. Using a thematic analysis, results indicate that 1) some LGBT individuals compartmentalize their sexual and religious identities through cost/benefit analysis and self-silencing and 2) others reconcile their two identities through broadening their concept of religion, emphasizing the relational connections with God, and distinguishing between Biblical literalists and God. Further, discussion of Spiral of Silence, Muted Group Theory, and Null Persona as the theoretical lenses are used to draw implications of these findings. This study seeks to open up dialogue concerning sexuality and religion in order to garner a more welcoming environment for LGBT Christians.
Keywords: Reconciliation; Sexual identity; Religious identity; LGBT; Self-concept; Communication (0459); GLBT Studies (0492); Religion (0318)